Glaukoma Sekunder pada Aniridia - Nintyastuti, Isna Kusuma (Jurnal Kedokteran, 2017)
A 12 year-old boy present with a history of slowly progressive blurred vision since 8 years ago. From the anamnesis revealed that his father and sister diagnosed as having secondary glaucoma due to aniridia. The visual acuity was 6/45 cc S-2,00D became 6/20 maximal for the right eye and 6/20, ccS-1,75D became 6/12 maximal. The anterior chamber was deep with pupil diameter 9 mm with a small iris stump. A subcapsular cataract was present. The cup-disc ratio was 0.5 with glaucomatous signs papil for the right eye and 0.4 for the left eye. The intraocular pressure was 36 mmHg for the right eye and 31 for the left eye. The gonioscopy examination result was closed angle for the both eye. The average thickness of the retinal nerve fiber layer was 103,82 µm and 90,42µm for the right and left eye respectively. The visual field examination for the right eye was very severe general depression with inferior acuate defect and for the left eye was severe general depression with nasal defect. The initial management was medical treatment with timolol 0.05% eyedrops followed by trabeculectomy with MMC application. A flat anterior chamber complication was found on the right eye and successfully treated with intracameral injection of sodium hyaluroniate 1.5% viscoelastic. The IOP was decrease immediately on the first day after surgery and well controlled until 6 months after surgery.